Analisis Selisih Biaya Bahan Baku Produk Terhadap Efisiensi Biaya Produksi Cock Pada Ud.Mixmex Kalikapas Lamongan - Nurcholidah, Lilik (Fakultas Ekonomi, Program Studi Akuntansi, 2019)
This research is a quantitative descriptive research and analyzes the difference between the cost of raw materials and the efficiency of production costs. There are two things to consider in connection with costs: 1) Costs are a measure of economic resources. The elements that represent the costs of producing goods and services are the physical amount of material, the number of units of time, and labor and the amount of quantity from other economic sources. 2) The size of the cost is translated into monetary units (money) The unit of money is a measure on a standard scale that unifies the size of the use of existing economic resources, so that the total use of economic resources can be measured. The formulation of this research problem is as follows: 1) What is the cost of raw materials for UD. MIXMEX UDC Kali Cotton Lamongan? 2) How is the cost efficiency of the production of COCK UD. MIXMEX Kali Cotton Lamongan? 3) How is the analysis of raw material costs to the efficiency of the production costs of COCK UD. MIXMEX Kali KapasLamongan ?. The sample data used is the financial statements, data analysis methods used by the author are: (1) Calculation of the difference in raw material prices (SHB) (2) Calculation of the Quantity Difference in Raw Materials (LCS). The difference in cost of ud.mixmex raw material in 2017 is Rp.236,831,514,346 per 2017 Then the production cost of UD.MIXMEX costs Rp. 452,817,337,394 as of 2017 Thus it can be obtained that the analysis of the difference in raw material costs to the efficiency of production costs is as much as the cost of raw materials Rp. 215,985,823,048 as of 2017.